El Nino Effect on Coffee Growth and Productivity on Several Agroforestry Systems in Gumitir Mountain Coffee Farms, East Java, Indonesia - Fitria Yuliasmara (Indonesian Coffee and Cocoa Research Institute, 2017)
Climate change and global warming have become major issues in the last 10 years and affect many sectors including coffee plantations. Global warming causes El Nino to occur more frequently and potentialy reduced agricultural production between 5–20%. In coffee plantations, an effort to minimize the impact of climate change is the use of agroforestry cropping pattern. One of the Robusta coffee producing areas grown using agroforestry system in East Java is at Gumitir mountain area. Coffee plants used as samples were 10–12 years old of Tugusari 6 coffee plantations managed by Sidomulyo farmer group. The environmental design used completely randomized block design with three replicates for each treatment which consisted of +0.5 ha. The results of this study indicated that coffee grown under forest produced the lowest irradiation and keep daytime tem-peratures 26.33oC with humidity 85% during this El Nino period. On plant growth parameters showed that the lower intensity of irradiation produced coffee plants with morphological characters of longer segments, larger leaves and higher chlo-rophyll content. Plant growth showed no significant difference except in coffee agroforestry system with pine which produced the smallest stem diameter and fewer productive branches. It was suspected due to the presence of allelopati compounds released by the litter of pine leaves. Coffee grown under natural forest produced highest nodes per branch, cherries per node, and number of cherries per tree than other systems. Productivity of robusta coffee in Gumitir mountain area during El Nino showed that the highest productivity in forest 1497 kg ha –1 and 1355 kg ha –1 on coffee grown under Leucaena, due to its ability to maintain moisture. Agroforestry system in coffee is able to maintain environmental conditions in this case in terms of irradiation, temperature and moisture during El Nino which caused stability of plant growth and coffee productivity during El Nino.